2015
DOI: 10.1002/jwmg.938
|View full text |Cite
|
Sign up to set email alerts
|

Combining waterfowl and breeding bird survey data to estimate wood duck breeding population size in the Atlantic Flyway

Abstract: We combined data from the Atlantic Flyway Breeding Waterfowl Survey (AFBWS) and the North American Breeding Bird Survey (BBS) to estimate the number of wood ducks (Aix sponsa) in the United States portion of the Atlantic Flyway from 1993 to 2013. The AFBWS is a plot-based survey that covers most of the northern and central portions of the Flyway; when analyzed with adjustments for survey time of day effects, these data can be used to estimate population size. The BBS provides an index of wood duck abundance al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Focusing on a temporal pattern, the modeled pattern of variation in this index is referred to as the population trajectory. In combination with population size surveys, BBS trajectories can be used to predict population sizes from areas of overlap and areas covered only by BBS data (Runge et al 2009, Millsap et al 2013, Zimmerman et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on a temporal pattern, the modeled pattern of variation in this index is referred to as the population trajectory. In combination with population size surveys, BBS trajectories can be used to predict population sizes from areas of overlap and areas covered only by BBS data (Runge et al 2009, Millsap et al 2013, Zimmerman et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…We found males had slightly higher harvest rates than females, and although not statistically significant, adult males and adult females had slightly lower harvest rates than their hatch-year counterparts as we hypothesized and other published studies have found (Johnson et al 1986). Zimmerman et al (2015) combined data from the Atlantic Flyway Breeding Waterfowl Survey and North American Breeding Bird Survey and estimated approximately 1.3 million wood ducks for the U.S. portion of the Atlantic Flyway. We are unaware of any other Lincoln estimates using harvest data for wood ducks other than Zimmerman et al (2015) and Bowers and Martin (1975), but considering continental spring breeding population estimates for several other common waterfowl species including mallards Anas platyrhynchos and blue-winged teal Anas discors reach well into the millions, state-wide estimates of several hundred thousand wood ducks seem plausible.…”
Section: Discussionmentioning
confidence: 99%
“…We used population size estimates during 1998-2017 from the eastern portion of the Waterfowl Breeding Population and Habitat Survey (WBPHS; Zimmerman, Sauer, Link, & Otto, 2012) (Zimmerman, Sauer, Fleming, Link, & Garrettson, 2015). At the time of our assessment, we had BBS data through 2015, so the available time series for wood duck breeding population estimates was limited to 1998-2015.…”
Section: Population Modellingmentioning
confidence: 99%